2021
DOI: 10.3389/fcimb.2020.620529
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lactobacillus in Female Infertility Via Modulating Sperm Agglutination and Immobilization

Abstract: Infertility has become a common problem in recent decades. The pathogenesis of infertility is variable, but microbiological factors account for a large proportion of it. Dysbiosis of vaginal microbiota is reportedly associated with female infertility, but the influence of normal vaginal microbiota on infertility is unclear. In this review, we summarize the physiological characteristics of the vaginal tract and vaginal microbiota communities. We mainly focus on the bacterial adherence of vaginal Lactobacillus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 112 publications
(156 reference statements)
2
18
0
1
Order By: Relevance
“…The vaginal microbiome has been studied in pregnancy ( Romero et al., 2014 : Mehta et al., 2020 ), cervical cancer ( Champer et al., 2018 ; Chambers et al., 2021 ; and infertility ( Zhang et al., 2021 ). Alteration in the vaginal ecology during which the commensal lactobacilli are reduced and displaced by the anaerobic species of the genera Gardnerella, Sneathia, Prevotella, Atopobium.…”
Section: Introductionmentioning
confidence: 99%
“…The vaginal microbiome has been studied in pregnancy ( Romero et al., 2014 : Mehta et al., 2020 ), cervical cancer ( Champer et al., 2018 ; Chambers et al., 2021 ; and infertility ( Zhang et al., 2021 ). Alteration in the vaginal ecology during which the commensal lactobacilli are reduced and displaced by the anaerobic species of the genera Gardnerella, Sneathia, Prevotella, Atopobium.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative genomic analysis of E. coli strains used in our study revealed the unique presence in E. coli ATCC 35218 of the chromosomal HlyE gene coding for hemolysinE (data not shown), a toxin with a short half-life that is known to impair membrane integrity in other cell types 40 . Therefore, it is possible that the detrimental effects of E. coli strain ATCC 35218 are mediated by more than one spermotoxic factor 41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many unexplained cases of infertility could also be attributed to the vaginal microbiome. Researchers have put forward many hypothesis to explain it, including the impact of vaginal bacteria on sperm motility, [ 25 ] bioactive metabolites of the vaginal microbiome entering the blood to cause fecundability reduction, [ 26 ] and the potential effect of the vaginal microbiome on the hypothalamic pituitary ovarian axis [ 27 ]. Although there is no direct evidence that M.hominis would impact female fertility through above three pathways, these hypotheses are also reasonable for M.hominis .…”
Section: Discussionmentioning
confidence: 99%